Odpowiedzi

Najlepsza Odpowiedź!
2010-03-13T12:20:25+01:00
A)x²+y²=4
x²+y²=2²
(x-0)²+(y-0)²=2²
S=(0,0), r=2,
gdyż równanie okręgu jest takie:
(x-a)²+(y-b)²=r², gdzie S=(a,b) - środek okręgu; r- promień okręgu

b)(x-4)²+(y+1)²=5
S=(4,-1), r=sqrt[5] /pierwiastek z 5/

c)x²+y²-2y=0
x²+(y-1)²-1=0
x²+(y-1)²=1
S=(0,1), r=1

d)x²+y²-4x+6y+1=0
(x-2)²+(y+3)²-4-9+1=0
(x-2)²+(y+3)²-12=0
(x-2)²+(y+3)²=12
(x-2)²+(y+3)²=(sqrt[12])²
S=(2,-3), r=sqrt[12]=2sqrt[3]


e)x²+y²+3x-y+1=0
x²+3x+y²-y+1=0
(x+3/2)²+(y-1/2)²-9/4-1/4+1=0
(x+3/2)²+(y-1/2)²-10/4+1=0
(x+3/2)²+(y-1/2)²-6/4=0
(x+3/2)²+(y-1/2)²=6/4
S=(-3/2;1/2), r=sqrt[6]/2